Making the Internet Safe for Gadgets. - Geller, Tom (Communications of the ACM, 2013)
The article reports on the Future Internet Architectures (FIA) program of the U.S. National Science Foundation (NSF). The program is considered as an attempt to design a future Internet to meet the challenges of the 21st century such as the increasing number of mobile devices and sensors. A two-part naming system for network objects is described in the FIA-funded MobilityFirst project. Information is also presented on the Named Data Networking (NDN) project, which originally used the CCNx open-source reference implementation codebase.